Pengaruh Penambahan Bioaktivator Propunic Terhadap Kualitas Pupuk Organik Cair Urin Sapi dan Limbah Cair Tahu - Chalisty, Vian Dwi; Baharudin, Mohamad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The study aimed to determine the effect of the addition of Propunic bioactivator on the quality of liquid organic fertilizer (POC) from cow urine and tofu liquid waste. The materials used in the study were 100 liters of Simmental cow urine, 300 liters of tofu liquid waste obtained from a tofu factory in Glontor Village, Karanggayam District, Kebumen Regency, Central Java, molasses, and Propunic bioactivator from CV Pendawa Kencana Multifarm. The addition of Propunic to each treatment was P0 (0%), P1 (0.5%), P3 (1%), and P4 (1.5%). Each treatment had 5 replications. All materials were mixed and fermented in a fermenter barrel for 15 days. The variables observed included pH, total N content, color, and aroma. Data on pH and total N content were analyzed using a complete unidirectional pattern design and if there was a significant difference, a Duncan further test was carried out. Color and aroma parameters were analyzed using Kruskal Wallis. The results showed that the pH after fermentation decreased at P1 (3.62), P2 (3.46), and P3 (3.72). The low pH value observed in the treatment with bioactivators was due to the ample substrate and the significant production of organic acids by lactic acid bacteria during fermentation up to the 15th day. The control treatment (P0) experienced an increase in pH from 5.65 to 5.93. The total N content in each treatment was still below the Permentan standard, namely P0 (0.040%), P1 (0.029), P2 (0.031), and P3 (0.038%). The color quality in the P0 treatment produced a slightly brown color, while the P1, P2, and P3 treatments produced a brown color. The aroma in P0 produced an unpleasant odor, P1 and P2 had a pleasant aroma, and P3 had a slightly pleasant aroma. Based on the research that has been done, it can be concluded that adding bioactivators produces the physical quality of POC in the form of good color and aroma marked by a brown color and a pleasant aroma. The chemical quality of POC cow urine and tofu liquid waste without adding bioactivators can produce a pH value of 5.93 which meets the quality standards and the highest total N content of 0.040%. Therefore, the production of POC from cow urine and tofu liquid waste, without the addition of bioactivators, can achieve a pH that meets the quality standards of the Permentan, but it does not satisfy the recommended total N content. The suggestion that can be given in this study is that to increase macronutrients according to quality standards, a more complete composition of POC materials is required